Constructing Political Image in the Mediatized Era: Personal Branding of Indonesian Party Chairmen on Social Media - Dimas Subekti; Dinda Rosanti Salsa Bela; Azira Novia Rizal; Suci Rahmadani (INJECT (Interdisciplinary Journal of Communication), 2026)
This research aims to analyze the digital personal branding strategies of the chairpersons of the Democratic Party, PKB, and PAN on TikTok. This research uses a qualitative method with a comparative case study approach. The findings of this study indicate that Agus Harimurti Yudhoyono tends to use a formal communication style and content focused on political and professional activities, reflecting an image of institutional and professional leadership. Muhaimin Iskandar demonstrates a more balanced, integrative communication pattern by combining formal, informal, symbolic, and emotional elements with diverse content narratives. Meanwhile, Zulkifli Hasan emphasizes informal and entertainment content, demonstrating a strong adaptation to TikTok's participatory culture. In terms of public response, Agus Harimurti Yudhoyono received mostly positive sentiment, while Muhaimin Iskandar and Zulkifli Hasan showed more varied sentiment patterns. Differences were also found in posting frequency strategies, ranging from momentum-based communication to consistent digital presence. Overall, this research shows that digital personal branding among Indonesian political leaders is diverse and reflects different approaches to political personalization in the digital era. This research highlights the increasing importance of social media in shaping political image, public engagement, and leadership legitimacy in contemporary Indonesian politics.